Contribuições das ruralidades para a Psicologia Brasileira - Sousa, Dyullia Moreira de (2025)
Brazil has developed under strong agrarian influences, not only in economic and political matters but also in the subjectivity of its people. On the other hand, psychology as it was disseminated in the country initially focused on issues related to large cities, due to rural exodus and modernization, leaving a non-urban population marginalized. Rural populations are an example of groups that have been made invisible over time by Psychology, only receiving proper attention with the emergence of Rural Psychology. For that reason, this study is guided by the question: how can Rural Psychology help in building a Brazilian psychology that aligns with reality, especially that of rural populations? The general objective is to outline the contributions of ruralities to Brazilian Psychology. Based on the assumption that if Brazil has agrarian roots, then to construct a psychological theory for the country, it is necessary to consider the rural heritage of the Brazilian people. To that end, an exploratory bibliographic research was conducted using the Pepsic, Scielo, and Lilacs databases, with descriptors such as "rural," "agrarian," and "peasant." This allowed for mapping the state of the art, revealing both the thematic diversity of works in rural psychology and the scarcity of epistemological discussions. For the analysis, 12 articles were selected that address expressions of the social question in the countryside, psychic and subjective constitution in rural settings, and theoretical-methodological aspects of a "rural psychology." It is concluded that it is not possible to work with rural populations from a psychology that is markedly urban. However, the goal is not to create a separate Rural Psychology, which would increase the dichotomy between rural and urban. Therefore, it is advocated that rurality must be considered in the development of a Brazilian psychological theory, in order to truly encompass the population’s diversity, including rural peoples.